Kompas Digital News Kesatuan Dan Keterpaduan Komdigi Peringatan Kepada Tiktok Dan Roblox Untuk Membatasi Akun Anak-Anak - Astri Rahmah Aulia; Nurlela; T. Thyrhaya.Zein (Universitas Muhammadiyah Surabaya, 2026)
Discourse analysis of popular news is a crucial step in understanding the comprehensibility of information in mass media. This study analyzes the formal and semantic aspects of a news article titled